2004
DOI: 10.1037/1053-0479.14.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Cognitive Therapy for Depression: A Preliminary Investigation.

Abstract: This study is a preliminary investigation of an integrative treatment aimed at improving the efficacy of cognitive therapy (CT) for depression. The development of the treatment protocol was based on process findings, which suggested that strategies used in CT to resolve alliance ruptures may actually exacerbate problems in the therapeutic relationship. The protocol integrates, within the traditional CT treatment manual, procedures to repair alliance ruptures that are derived from or consistent with humanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 39 publications
1
73
0
Order By: Relevance
“…This is a not-uncommon phenomenon when testing a new therapy, with the first studies showing large magnitude effects (also called the "winner's curse"). It is worth noting that some more recent studies also found large ESs of CBT (Castonguay et al, 2004;David, Szentagotai, Lupu, & Cosman, 2008;Quilty, Dozois, Lobo, Ravindran, & Bagby, 2014). Although it would be impossible to exclude with absolute certainty the possibility that year of publication might be systematically related to the effects of CBT for depression, for some outcomes in some circumstances, this is not very probable.…”
Section: Discussionmentioning
confidence: 94%
“…This is a not-uncommon phenomenon when testing a new therapy, with the first studies showing large magnitude effects (also called the "winner's curse"). It is worth noting that some more recent studies also found large ESs of CBT (Castonguay et al, 2004;David, Szentagotai, Lupu, & Cosman, 2008;Quilty, Dozois, Lobo, Ravindran, & Bagby, 2014). Although it would be impossible to exclude with absolute certainty the possibility that year of publication might be systematically related to the effects of CBT for depression, for some outcomes in some circumstances, this is not very probable.…”
Section: Discussionmentioning
confidence: 94%
“…Castonguay and colleagues added humanistic and interpersonal strategies to standard CT to repair ruptures in the working alliance and found this integrative approach superior to a wait list control in one study [153] and superior to standard CT in a second. [154] While the approach is not wholly experiential in nature and the studies relied on relatively inexperienced graduate student therapists, these findings do suggest that humanistic and interpersonal strategies might be a useful adjunct to CT.…”
Section: Resultsmentioning
confidence: 99%
“…My practice has in turn influenced my research. Along with some of the research findings mentioned above, my experience with successful and unsuccessful cases has substantially informed the studies on integrative therapy for depression (Castonguay, Schut, Aikins, et al, 2000) and generalized anxiety disorder (Newman, Castonguay, Borkovec, & Molnar, in press) in which I am currently involved.…”
Section: Why Is It Important To Have Practitioners Conducting Researcmentioning
confidence: 91%